Lead Selective Zirconium(IV) Sulphosalicylomolybdate as Three Component Ion Exchanger - Jeena, V.R.; Janardanan, C. (Asian Journal of Chemistry, 2012)
A three component inorganic ion exchanger zirconium(IV) sulphosalicylomolybdate has been prepared under varying conditions. Characterization of the exchanger was done by determining ion exchange capacity, distribution coefficient for various metal ions, chemical analysis, pH titration, IR Spectra and thermal analysis. The distribution coefficients (Kd) of 10 metal ions were determined. On the basis of difference in distribution coefficients, some analytically important binary (Cd2+/Pb2+, Zn2+/Pb2+, Ca2+/Pb2+, Th4+/Pb2+, Cd2+/Cu2+, Zn2+/Cu2+ and Th4+/Cu2+) and ternary (Th4+/Ni2+/Pb2+, Th4+/Co2+/Pb2+, Th4+/Cd2+/Pb2+) separations of metal ions have been achieved. The significance of the exchanger is revealed by the important separations carried out from wastewater collected from spinning and weaving mills near Kannur.